Rural and urban employment patterns in Brazil: a dynamic panel data approach - Paulo, Evanio Mascarenhas; Tabosa, Francisco José Silva (Interações, 2018)
This study applies a quantitative approach in dynamic panel data to capture the determinants of employment quality in Brazil through the model of generalized minimum moments. The results show that the rural universe persists as a more precarious environment than urban areas, although the differences has decreased with time. In addition, the results of this study show that growth of labor income and the level of education of employees are important tools not only to expand the levels of job quality, but also as response to dilemmas of the surveyed labor markets.